Carbon dots for highly effective photodynamic inactivation of multidrug-resistant bacteria. Issue 3 (5th May 2020) - Abu Rabe, Dina I.; Mohammed, Oluwayemisi O.; Dong, Xiuli; Patel, Amankumar K.; Overton, Christopher M.; Tang, Yongan; Kathariou, Sophia; Sun, Ya-Ping; Yang, Liju
Abstract : Effective photodynamic inactivation of MDR bacteria by CDots. Abstract : For addressing the ever increasing challenge of multidrug-resistant (MDR) bacterial infections, specifically designed and prepared carbon dots (CDots) of small carbon nanoparticles with surface functionalization–passivation by oligomeric polyethylenimine were found to be readily activated by visible light to effectively and efficiently inactivate MDR bacterial strains. The inactivation was evaluated under various combinations of experimental conditions (dot concentrations, light intensities, and treatment times), with the results collectively suggesting CDots as a new class of promising agents for combating MDR bacteria. Mechanistic origins and implications of the observed strong antibacterial actions as relevant to the photoexcited state processes in CDots and the photodynamically induced cellular damages leading to the death of the bacterial cells were explored, with the results discussed.